La pandemia del nuovo coronavirus 2019 ed il trapianto renale - Aris Tsalouchos; Maurizio Salvadori (AboutScience Srl, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major pandemic challenging health care. Infection has been reported in all ages, but older patients and immunosuppressant patients as the transplanted are at major risk. Prevention and treatment, whenever possible are the commonly used strategies. Three steps may be distinguished. In the first step prophylaxis is essential and based in avoiding any possible contact to infected people. Staying at home, masking the patient, carefully washing the hands are the most commonly used strategies. If the disease develops in  a transplanted patient two steps must be added. In the first step the reduction of the immunosuppressive therapy must be considered together with the administration of antiviral drugs. In a second phase of the disease a severe lung involvement may develop mostly due to a inflammation citokine induced. In this phase in addition to a intensive ventilation requiring the intensive care unit, anticytokine drugs as tocilizumab should be considered.